Determinants of awareness on sexual harassment at workplace in public and private sector at Melaka Tengah / Nurul Atikah Nazri - Nazri, Nurul Atikah (Faculty of Business and Management, 2018)
This study are focusing on awareness on sexual harassment at workplace in public and private sector at Melaka Tengah. The purpose of the study is to examine the relationship between mass media, attitude, training and education with awareness on sexual harassment at workplace. Questionnaires and sample random sampling are used as method of this study. The finding result shows mass media and attitude has significant with awareness on sexual harassment except training and education was does not significant with the awareness on sexual harassment at workplace.